Somatic genetic changes accompanying lung tumor development. - Foster, N; Banerjee, A; Xian, J; Roberts, I; Pezzella, F; Coleman, N; Nicholson, A; Goldstraw, P; George, J; Rabbitts, P (2005)
Carcinomas are believed to develop by incremental steps of increasingly abnormal morphology driven by accumulating somatic genetic changes. This process is often difficult to study, as the early stages are undetectable. We used fluorescence bronchoscopy, which enhances detection of preinvasive bronchial lesions, and have obtained sequential biopsies of carcinoma in situ (CIS) from a patient with no detectable tumor and from a squamous cell carcinoma that developed 19 months after presentation at the site of one of the previous CIS lesions. Biopsies of preinvasive CIS, which follow-up showed had different pathologic outcomes, and tumor were microdissected to obtain enriched cell populations and DNA prepared from them. Molecular characteristics of these biopsies were compared by loss of heterozygosity analysis, TP53 mutation analysis, and comparative genomic hybridization. Although all lesions examined had the same TP53 mutation and almost identical allelotypes, differences were observed. Loss in 5q21 and amplification of 3q25-26 were associated with the lesion that progressed and the subsequent carcinoma. Allele loss at 4p16 was detected in the tumor but not in any of the CIS lesions, suggesting it was a late event associated with tumor invasion. Amplification at 4q12 was specifically observed in the tumor and in the CIS at the site of eventual tumor formation. Although these findings may be unique to this one patient, the successful demonstration of sequential genetic changes raises the possibility that this approach, unencumbered by interpatient variability between lesions, will greatly facilitate the identification of molecular events driving the invasive process